2001
DOI: 10.1034/j.1600-0455.2001.042002234.x
|View full text |Cite
|
Sign up to set email alerts
|

UTERINE ARTERY EMBOLIZATION OF SYMPTOMATIC UTERINE FIBROIDS. Initial success and short-term results

Abstract: UAE is a method with a high technical success rate. The treatment has good effect on fibroid volume reduction and clinical symptoms. Severe post-procedural pain occurs generally in successful bilateral embolizations, but complications and adverse events are otherwise few and minor. UAE represents a promising new method for treating uterine fibroid-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…The reduction in the dominant fibroid volume in our study was comparable to these studies with a mean volume of 69.4 cm 3 before UFE and 41.4 cm 3 after UAE, which resulted in a 40.1% volume reduction ( P < 001). [ 22 ] Similar observations were also made by Andersen et al,[ 25 ] Spies and colleagues,[ 26 ] and Walker and Pelage,[ 27 ] who reported ranges between 35% and 55%.…”
Section: Discussionsupporting
confidence: 79%
“…The reduction in the dominant fibroid volume in our study was comparable to these studies with a mean volume of 69.4 cm 3 before UFE and 41.4 cm 3 after UAE, which resulted in a 40.1% volume reduction ( P < 001). [ 22 ] Similar observations were also made by Andersen et al,[ 25 ] Spies and colleagues,[ 26 ] and Walker and Pelage,[ 27 ] who reported ranges between 35% and 55%.…”
Section: Discussionsupporting
confidence: 79%
“…Since the first case reports by Ravina, et al, this procedure has been shown to be safe and effective [2,35]. In UAE studies using permanent microspheres as an embolic, fibroid volume decreased by 53.4 卤 26.9%, 3 months after UAE, by 63.7 卤 28.2% after 6 months, and by 71.8 卤 26.8% after 12 months [36,37]. Randomized comparative trials of embolics have shown differences in infarction rate between the different commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…30 We used, on average, two particle flasks, perhaps because of the elasticity of the use of different particle sizes, or because we established technical success when we observed the absence of flow and retention of contrast in the uterus, known as the parenchymatous phase of embolization, an event that sometimes varies from one report to another. 30 From a technical viewpoint, we observed the importance of the gynecologist's participation in the judicious selection of cases, explaining the technique to be adopted for the patient, answering patients' queries and, especially, transmitting security through his presence on the day of the procedure. In addition, the increasing experience and consequent greater skill of the operating radiologist may lead to more rapid embolization procedures, with gradually reduced exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%